EVALUASI DUA PRODUK RENCANA TATA RUANG WILAYAH DI KECAMATAN KUPANG TIMUR, KABUPATEN KUPANG, NUSA TENGGARA TIMUR - , ADVENT NUGRAHENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spatial planning is one of government policy which can control the land use. The presence of two products of spatial plan which was overlapping each other in the same location, cause mismatch of referral functions with actual land use. The goals that want to be achieved in this research are (1) To identify the scale of overlapping between the new capital of regencyâs spatial plans and agropolitan region, (2) To identify the variety of land use in the overlapping region, (3) Asses the distribution of land use, and (4) Offer the alternative solution for the right referral functions of land use accordance with the spatial plan of the new capital. The method used in this research is the comparison map allocation of land utilization of the capital region and agropolitan region with overlay analysis in the geographic information systems. The sampling method using stratified random sampling. The data analysis using overlay analysis within GIS and crosstabs. The new capital of regencyâs region possesses overlapping region with agropolitan region. Amounting to 87.48% overlap area already have the same type of land utilization between the second plan with the referral as dry land farming areas. The actual type of land use is dominated by brushwood, so the direction of the land utilization in accordance with the spatial plan of the new capital area is as dry land farming areas. There are land use thatâs not aligned with the direction of the new land utilization of the capital region plan. It has an opportunity over the land which is not in accordance with the plan that the government needs to do a review of two regional spatial planning, so that there is no dual use directives and to oversee land untapped